178. Impact of a microbiology comment nudge on the diagnostic evaluation of Staphylococcus aureus bacteriuria. (15th December 2022) - Patel, Dimple; Bandali, Aiman; Giordano, Pamela; Kessler, Jason; Roland, Robert
Abstract: Background: Staphylococcus aureus is a relatively uncommon cause of urinary tract infections. S. aureus bacteriuria is thought to result most commonly from urinary tract instrumentation (ascending infection) or via hematogenous seeding of the genitourinary tract (descending infection). Given the devastating impact of invasive S. aureus infection and awareness that S. aureus bacteriuria is often a marker for S. aureus bacteremia, growth of S. aureus from urine cultures should prompt urgent clinical assessment, including blood culture collection. In April 2021, a comment nudge was added to the microbiology culture and susceptibility report for all S. aureus isolated from urine cultures performed at the Atlantic Consolidated Laboratory (ACL) at Atlantic Health System. The purpose of this study is to assess the impact of a comment nudge on the diagnostic evaluation of S. aureus bacteriuria. S. aureus bacteriuria comment nudge Methods: All patients with S. aureus bacteriuria were retrospectively identified from the ACL microbiology database. The primary endpoint was collection of blood cultures within 96 hours of positive urine culture during the 6-month period pre-comment (October 2020 – April 2021) compared to 6-month period post comment (May 2021 – November 2021). In addition, incidence of S. aureus bacteremia among the patients with collected blood cultures was also evaluated. Results: S. aureus bacteriuria was identified in 122 patients during the Pre-Comment period and 188 patients in the Post-Comment period. Blood cultures were collected more frequently in the Post-Comment period compared to the Pre-Comment period (64% vs. 51%, p=0.018). Among patients for whom blood cultures were collected, 29% had concomitant S. aureus bacteremia in the Pre-Comment period compared to 16% in the Post-Comment period (p=0.03). Conclusion: The addition of a comment nudge to the microbiology report of urine cultures growing S. aureus significantly improved follow-up blood culture collection. Health systems may consider implementation of similar interventions, particularly in resource-limited settings, to avoid delayed recognition of S. aureus bacteremia. Disclosures: All Authors : No reported disclosures.